Elucidation of DnaE as the Antibacterial Target of the Natural Product, Nargenicin. Issue 10 (22nd October 2015) - Painter, Ronald E.; Adam, Gregory C.; Arocho, Marta; DiNunzio, Edward; Donald, Robert G.K.; Dorso, Karen; Genilloud, Olga; Gill, Charles; Goetz, Michael; Hairston, Nichelle N.; Murgolo, Nicholas; Nare, Bakela; et al.
Summary: Resistance to existing classes of antibiotics drives the need for discovery of novel compounds with unique mechanisms of action. Nargenicin A1, a natural product with limited antibacterial spectrum, was rediscovered in a whole-cell antisense assay. Macromolecular labeling in both Staphylococcus aureus and an Escherichia coli tolC efflux mutant revealed selective inhibition of DNA replication not due to gyrase or topoisomerase IV inhibition. S. aureus nargenicin-resistant mutants were selected at a frequency of ∼1 × 10 −9, and whole-genome resequencing found a single base-pair change in the dnaE gene, a homolog of the E. coli holoenzyme α subunit. A DnaE single-enzyme assay was exquisitely sensitive to inhibition by nargenicin, and other in vitro characterization studies corroborated DnaE as the target. Medicinal chemistry efforts may expand the spectrum of this novel mechanism antibiotic. Highlights: Nargenicin inhibited DNA synthesis in macromolecular labeling studies Resistance mutation mapped to dnaE and was necessary and sufficient for resistance Nargenicin inhibited a DnaE single-enzyme assay DNA promoted binding of nargenicin to S. aureus DnaE but not E. coli DnaE Abstract : There is an urgent need for new antibiotics due to continuing emergence of resistance. Painter et al. identified the antibacterial mechanism of nargenicin: inhibition of the replicative bacterial polymerase DnaE. This is the first known example of such an inhibitor.